Quality Analysis of HQMS Direct Network Report of the First Page of 12, 367 Medical Records. (March 2014) - Xiao, Xiaolan; Zuo, Chuantian; He, Haiping; Zhao, Jie; Gu, Juzhen; Qin, Lili; Lu, Fenghai; Liang, Jian
Abstract Objective. To standardize the filling of the first page of medical records and improve the information quality of the Hospital Quality Monitoring System (HQMS) network report. Methods. According to the filling requirements and selection principles for the main diagnosis of diseases as specified in the tenth edition of International Classification of Diseases (ICD-10), the quality of the first page is analyzed in accordance with the standards in the Filling Criterion of Medical Records in Guangxi and the data reporting requirements for the first page of medical records in the HQMS. The filling quality of the first page of medical records directly reported via information networks currently is analyzed in the article. Results. Of the 12, 367 medical records, a total of 2, 819 medical records have defects, accounting for 22.80%. The defect types are as follows: basic information (16.99%), discharge diagnosis (20.01%), surgery and operation (21.67%), the classification of diseases and surgical operations (8.90%), and delayed signature of three-level doctors (28.80%), other errors (3.62%). Conclusion. We should arrange for standardized on-the-job training for clinicians, medical record coders and other relevant personnel; and we should establish the hospital/clinical department two-level quality monitoring system for the first page of medical records, add medical record quality control positions and take other measures to improve the quality of the first page of medical records.